PERAN GURU DALAM PEMBELAJARAN DARING BAGI ANAK USIA DINI ERA PANDEM COV ID-191 - Shofiyati; Sumiyati Sumiyati; Eka Novita Candra (UIR PRESS, 2022)
Abstract During the COVID-19 pandemic, as is currently the case, various activities are limited not only in office activities but also teaching and learning activities are also limited, so that education which is usually carried out face-to-face or offline must be carried out using the distance education method or called online. This study uses qualitative methods and data analysis in this study will use a qualitative verification which is carried out in three steps, namely data reduction, data presentation and conclusion drawing. The data reduction process includes the selection process, focusing on data simplification, abstraction and transformation of rough data obtained in the field. The objects in this research are educators, parents, students at RA Al Jauhariyyah Kajen. The results of this study are the role of educators in the implementation of distance/online learning is not only preparing material for students, but also being communicators who play an active role in guarding parents in accompanying children during the online learning process. Online learning plans have been designed in such a way and involve parents in determining competencies/indicators during online learning, designing children's activities, materials and children's learning resources prepared by the institution to make it easier for parents to accompany children during online learning. Keywords: Online learning, early childhood, covid-19